2011
DOI: 10.1103/physrevb.84.024202
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-cation LixAg1xPO

Abstract: We show that NMR stimulated-echo experiments provide detailed information about the jump dynamics of each of the ionic species in mixed mobile ion glasses. The potential of this technique is exploited to measure two-time correlation functions of the lithium and silver ionic hopping motions in Li x Ag 1−x PO 3 glasses. Comparison of stimulated-echo decays from 6 Li or 7 Li NMR with that from 109 Ag NMR shows that the residence times at the ionic sites are significantly longer for the respective minority compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…More detailed insights into the mixed cation effect of Li x Ag 1−x PO 3 glasses are available when analyzing the dependence of the 6 Li and 109 Ag NMR 2T-CF on temperature and composition. These results will be published elsewhere [41]. Below, we will use 6 Li and 109 Ag NMR 3T-CF to investigate the origin of the nonexponential ionic relaxation in Li 0.5 Ag 0.5 PO 3 glass.…”
Section: Nmr Two-time Correlation Functionsmentioning
confidence: 99%
“…More detailed insights into the mixed cation effect of Li x Ag 1−x PO 3 glasses are available when analyzing the dependence of the 6 Li and 109 Ag NMR 2T-CF on temperature and composition. These results will be published elsewhere [41]. Below, we will use 6 Li and 109 Ag NMR 3T-CF to investigate the origin of the nonexponential ionic relaxation in Li 0.5 Ag 0.5 PO 3 glass.…”
Section: Nmr Two-time Correlation Functionsmentioning
confidence: 99%
“…Inspired by the pioneering theoretical and experimental studies of Wu et al and Bçhmer et al, spin-alignment NMR spectroscopy was then used to characterize lithium diffusion in a number of materials in different structural forms. For example, Li dynamics have been studied in: 1) single crystals of b-eucryptite (LiAlSiO 4 ) [30,39] and Li 3 N; [54] 2) polycrystalline materials such as the hexagonal [38,40] and cubic form of Li x TiS 2 , [55] Li 4 Ti 5 O 12 , [56] Li 4 SiO 4 , [49] Li 7 BiO 6 , [41] the aluminosilicate LiAlSi 2 O 6 , [45] and the garnet Li 5 La 3 Nb 2 O 12 ; [57] 3) nanostructured materials such as Li x TiO 2 nanowires; [58,59] and 4) highly disordered ceramics and glasses such as LiPO 3 [60] and the cation-mixed glass Li x Ag 1Àx PO 3 (0 x 1) [43] as well as b-spodumene LiAlSi 2 O 6 , [45,61] amorphous LiNbO 3 [62] and the glass ceramic Zerodur M. [63] Recently, longrange Li transport parameters have also been probed in Li 2 TiO 3 , which is, in its crystalline form, an extremely poor ionic conductor. [64] It is worth mentioning that Vogel et al used 109 Ag stimulated-echo NMR spectroscopy to record two-and four-time correlation functions.…”
Section: Introductionmentioning
confidence: 99%
“…In this way they studied silver dynamics in several crystalline [65,66] and glassy materials [67][68][69][70][71] including the aforementioned Li x Ag 1Àx PO 3 . [43] By using 109 Ag NMR spectroscopy they took advantage of site-specific chemical shift interactions to differentiate between magnetically nonequivalent silver ions. Vogel and co-workers clearly showed that the diffusion parameters probed by 109 Ag NMR stimulated echoes agree with those deduced from dc-conductivity measurements [65] that are sensitive to long-range transport of silver ions.…”
Section: Introductionmentioning
confidence: 99%
“…This (single-spin) correlation function, which is given by the NMR spin-alignment echo height S 2 vs. t m , contains the information about the probability of finding a spin, which was exposed to o Q at t 0 = 0, in the same state, i.e., exposed to the same quadrupole frequency, at a later time t 0 = t m . [16][17][18][19]23,25,52,56,57 In many cases S 2 , which is here given by…”
mentioning
confidence: 99%